The Specificity of Negotiations with a Russian Partner - Podolas, Izabela (The Copernicus Journal of Political Studies, 2018)
Cultural differences impede the process of communication and negotiation. When negotiators come from different cultural backgrounds, the risk, that there is no agreement exists, increases manifold. Negotiations with the Russians are the art of becoming friends. All preconceptions that may over-emphasize the fear of starting a relationship with a Russian partner disappear after first successful negotiations, because Russia has an incredible power of attraction that cannot be explained. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762